2022
DOI: 10.1097/md.0000000000031405
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of risk factors for intensive care unit acquired weakness

Abstract: Background: The aim of this meta-analysis is to systematically evaluate and summarize the risk factors of intensive care unit acquired weakness (ICU-AW), to provide evidence-based evidence for the formulation of prevention strategies for ICU-AW.Methods: PubMed, EMBASE, Web of Science, CBM (China Biology Medicine, China), Chinese National Knowledge Infrastructure, Chinese WANFANG, and VIP will be searched to define relevant risk factors for ICU-AW. The databases search period is from January 1, 2005 to August 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Several risk factors are associated with CIW, with the main ones being prolonged inflammatory status [ 11 13 ], multiorgan failure, prolonged mechanical ventilation, and ICU length of stay [ 14 ]. As evidence, severity scores correlate highly with CIW [ 15 ].…”
Section: Critical Illness Weaknessmentioning
confidence: 99%
“…Several risk factors are associated with CIW, with the main ones being prolonged inflammatory status [ 11 13 ], multiorgan failure, prolonged mechanical ventilation, and ICU length of stay [ 14 ]. As evidence, severity scores correlate highly with CIW [ 15 ].…”
Section: Critical Illness Weaknessmentioning
confidence: 99%
“…Another meta-analysis targeting five cohort studies also suggested a possible association between the use of NMBAs and ICU-AW (OR: 1.43, 95%CI: 0.92-2.22, I 2 = 0%). 85 Although these observational studies suggest a possible relationship between NMBAs and ICU-AW, the lack of intervention studies means that a clear causal relationship between NMBAs and ICU-AW is still unclear, and further research is needed.…”
Section: Neuromuscular Blocking Agentsmentioning
confidence: 99%
“…In this meta‐analysis, NMBAs were divided into benzyl quinolinic NMBAs (atracurium and cisatracurium) and amino‐steroid NMBAs (vecuronium and pancuronium) and their relationship with ICU‐AW was (OR: 14.79, 95% CI: 1.19–183.84, I 2 = 82%) and (OR: 3.68, 95% CI: 1.51–9.00, I 2 = 37%), respectively. Another meta‐analysis targeting five cohort studies also suggested a possible association between the use of NMBAs and ICU‐AW (OR: 1.43, 95%CI: 0.92–2.22, I 2 = 0%) 85 . Although these observational studies suggest a possible relationship between NMBAs and ICU‐AW, the lack of intervention studies means that a clear causal relationship between NMBAs and ICU‐AW is still unclear, and further research is needed.…”
Section: Drugs or Drug Prescriptions That May Lead To Sarcopenia Or M...mentioning
confidence: 99%
“…ICU-AW has been associated with increased mortality, reduced physical function and reduced health-related quality of life [6,19,20]. Risk factors for developing ICU-AW include female sex, mechanical ventilation days, age, infectious disease, increased organ failure score, hyperglycaemia and renal replacement therapy [21 ▪ ]. Assessing ICU-AW at the bedside continues to be a useful clinical tool to identify patients with increased care requirements in hospital and after hospital discharge [1,22].…”
Section: Icu-acquired Weakness and Patient-centred Outcomesmentioning
confidence: 99%